Differing Roles of Hyaluronan Molecular Weight on Cancer Cell Behavior and Chemotherapy Resistance - Price, Zoe K. (Cancers (Basel), 2018)
Hyaluronan (HA), a glycosaminoglycan located in the extracellular matrix, is important in embryo development, inflammation, wound healing and cancer. There is an extensive body of research demonstrating the role of HA in all stages of cancer, from initiation to relapse and therapy resistance. HA interacts with multiple cell surface receptors, including CD44, receptor for hyaluronan mediated motility (RHAMM) and intracellular signaling pathways, including receptor tyrosine kinase pathways, to promote the survival and proliferation of cancer cells. Additionally, HA promotes the formation of cancer stem cell (CSC) populations, which are hypothesized to be responsible for the initiation of tumors and therapy resistance. Recent studies have identified that the molecular weight of HA plays differing roles on both normal and cancer cell behavior. This review explores the role of HA in cancer progression and therapy resistance and how its molecular weight is important in regulating CSC populations, epithelial to mesenchymal transition (EMT), ATP binding cassette (ABC) transporter expression and receptor tyrosine kinase pathways.